The internal control model of Islamic Boarding School Salafiyah Syafi’iyah - Siti Maria Wardayati; Gunarianto Gunarianto; Abd. Mujib (Universitas Islam Negeri Walisongo Semarang, 2022)
Purpose - This research aims to find out the typical internal control practices rooted in the Salafiyah Syafi'iyah Sukorejo Islamic Boarding School (SSSIBS) and is offered to be a new model of internal control characterized with the unique values of the Islamic Institution (II).Method - This research uses a qualitative approach. The data are collected through observation, documentation, and interviews. These data collection techniques are carried out in two stages with 18 informants considered having sufficient experience in their departments, and good understanding of the research context.Result - The results found that the main element of the uniqueness of the SSSIBS is the spiritual value that underlies all activities in the II. In the element of spirituality, there are 4 categories, namely 1) the belief and attitude category, 2) practice category, 3) management category, and 4) IBS heritage category. All of these elements are bound as spiritual and become an effective fortress for the II in carrying out all its activities, and are known as Spiritual-based Internal Control.Implication - This research relates to leadership awareness on the importance of internal control to achieve the entity's goals, by constantly evaluating the understanding and implementation, and aligning them with spiritual values that characterize Islamic Institution.Originality - This research is the first study that reveals a new model of internal control in the SSSIBS.